Search for the exotic decay of the Higgs boson into two light pseudoscalars with four photons in the final state in proton-proton collisions at s = 13 TeV - Tumasyan, A. R.; Adam, Wolfgang; Andrejkovic, J. W.; Bergauer, Thomas; Chatterjee, Suman; Damanakis, Konstantinos; Dragicevic, Marko (Springer Science and Business Media Deutschland GmbH, 2023)
A search for the exotic decay of the Higgs boson to a pair of light pseudoscalars, each of which subsequently decays into a pair of photons, is presented. The search uses data from proton-proton collisions at s = 13 TeV recorded with the CMS detector at the LHC that corresponds to an integrated luminosity of 132 fb?1. The analysis probes pseudoscalar bosons with masses in the range 15–62 GeV, coming from the Higgs boson decay, which leads to four well-isolated photons in the final state. No significant deviation from the background-only hypothesis is observed. Upper limits are set on the product of the Higgs boson production cross section and branching fraction into four photons. The observed (expected) limits range from 0.80 (1.00) fb for a pseudoscalar boson mass of 15 GeV to 0.26 (0.24) fb for a mass of 62 GeV at 95% confidence level. © The Author(s) 2023.
Keywords: Hadron-Hadron Scattering; Higgs Physics